2019
DOI: 10.3390/bioengineering6040089
|View full text |Cite
|
Sign up to set email alerts
|

Development of High Cell Density Cultivation Strategies for Improved Medium Chain Length Polyhydroxyalkanoate Productivity Using Pseudomonas putida LS46

Abstract: High cell density (HCD) fed-batch cultures are widely perceived as a requisite for high-productivity polyhydroxyalkanoate (PHA) cultivation processes. In this work, a reactive pulse feed strategy (based on real-time CO2 or dissolved oxygen (DO) measurements as feedback variables) was used to control an oxygen-limited fed-batch process for improved productivity of medium chain length (mcl-) PHAs synthesized by Pseudomonas putida LS46. Despite the onset of oxygen limitation half-way through the process (14 h pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
(85 reference statements)
0
15
0
Order By: Relevance
“…Total biomass of 28.8 g L −1 and a PHA content of 61% (w/w) were achieved after 27 h using octanoic acid as the carbon source in a bioreactor operated under atmospheric conditions—resulting in final volumetric productivity of 0.66 g PHA L −1 h −1 . [ 157 ] As such, high‐cell‐density cultivation processes, combined with the synthetic biology, metabolic engineering, and systems biology approaches—as summarized in the previous sections of this review—can help to overcome the long‐standing problem of low PHA titers. This aspect is particularly important for producing novel biopolymers (which are typically accumulated in limited amounts) to achieve an economically competitive industrial scale.…”
Section: Fine‐tuning Of Pha Synthesis: Metabolic Engineering Approachmentioning
confidence: 99%
“…Total biomass of 28.8 g L −1 and a PHA content of 61% (w/w) were achieved after 27 h using octanoic acid as the carbon source in a bioreactor operated under atmospheric conditions—resulting in final volumetric productivity of 0.66 g PHA L −1 h −1 . [ 157 ] As such, high‐cell‐density cultivation processes, combined with the synthetic biology, metabolic engineering, and systems biology approaches—as summarized in the previous sections of this review—can help to overcome the long‐standing problem of low PHA titers. This aspect is particularly important for producing novel biopolymers (which are typically accumulated in limited amounts) to achieve an economically competitive industrial scale.…”
Section: Fine‐tuning Of Pha Synthesis: Metabolic Engineering Approachmentioning
confidence: 99%
“…The polyester biosynthesized by Pseudomonas putida ATCC47054 was isolated and purified to determine the PHA content using GC analysis and the PHA monomeric composition by 1 H-NMR, as listed in Table 1. The PHA productivity and product yield after 60-h cultivation were 0.067 g/L/h and 0.05 g PHA/g substrates, respectively, which is relatively low compared to other reports [27]. The chemical functional group analysis was performed using Fourier Transform Infrared Spectrophotometer (FTIR), as shown in Fig- ure 4.…”
Section: Productivity and Monomer Composition Of Mcl-pha From Pseudomonas Putidamentioning
confidence: 95%
“…Previous works have reported that the pulse feeding scheme was preferred than the continuous constant-feed technique yielding higher PHA accumulation. [23][24][25] The pulse feed strategy was better at cycling between carbon excess and carbon-limited conditions during fedbatch, hence enhancing PHA synthesis. In addition, during pulsefeeding condition, cell growth was less restricted compared to continuous feeding condition.…”
Section: Fed-batch Optimization With Doementioning
confidence: 99%